Application of Scientific Approach using Clustering and Fast Writing Techniques to Improve Folklore into Short Stories - Herniyastuti Herniyastuti; Nur Rahmi (Universitas Sembilanbelas November Kolaka, 2019)
This study aimed to describe the increase of the ability to develop folklore into short stories through a scientific approach with clustering and fast writing technique of students class X MIPA 1 at SMA Negeri 1 Watansoppeng. The approach in this study was qualitative. After conducting research using two cycles in the application of scientific approach with clustering and fast writing techniques, it was found that the application of the scientific approach with clustering and fast writing techniques for students in SMA Negeri 1 Watansoppeng could improve student learning outcomes in the material development of folktales into short stories.